Distribution of energy in p and S Seismic bodily waves (MAUSAM, 1966)
It is generally assumed that the energy in seismic bodily S waves is double that in the seismic bodily p waves. A theoretical explanation based on Debye's theory of specific heats o solids is suggested. The deduced result could also explain the observed fact that the wave frequency of p-waves is generally higher as compared to the wave frequency of S waves.